Impact of infection control educational activities on rates and frequencies of percutaneous injuries (PIs) at a tertiary care hospital in Saudi Arabia - Kamel El Beltagy; Aiman El-Saed; Mahmoud Sallah; Hanan H. Balkhy (Elsevier, 2012)
Objective: To study the impact of educational activities on the rates and frequencies of percutaneous injuries (PIs) at a tertiary care hospital in Saudi Arabia. Methods: PI surveillance is a routine activity in King Abdulaziz Medical City (a 900-bed teaching tertiary health care hospital) in Riyadh using the Exposure Prevention Information Network (EPINet) data collection tool. From 2001 through 2003, educational activities were conducted for health care workers (HCWs) to prevent PIs. The education included lectures on the risk of unsafe practices that may lead to PIs and how to avoid them. Data from before (1997-2000) and after (2004-2008) the intervention were imported from our surveillance system and statistically analyzed. Results: The total overall rate of PIs per 1000 HCWs was significantly lower in the post-intervention period than in the pre-intervention period (14 vs. 32.8/1000 HCWs, respectively). The rates of PIs among nurses and housekeepers showed a significant decrease (15 vs. 37.6/1000 HCWs and 10 vs. 34.5/1000 HCWs, respectively). The frequency of PIs in the emergency department (ED) and intensive care units (ICUs) showed a significant decrease (3.4% for both vs. 12.4% and 13.7%, respectively). PIs associated with devices, such as needles on IV lines, IV catheters, lancets and suture needles, showed a significant decrease. PIs occurring during device disassembly and from inappropriately discarded devices also decreased significantly. Conclusion: The educational program reduced some categories of PIs, including the overall rate, the rate among nurses and housekeepers, the frequency in the ED and ICUs and the frequency among needles on IV lines, IV catheters, lancets and suture needles. Other PI categories did not change significantly. Keywords: Percutaneous injuries, Education, Riyadh, Saudi Arabia